Synchronization of Power Grid by HVDC Technology - Sahu, Pankaj Kumar (Asian Journal of Electrical Sciences, 2018)
This research work expose the advantages of HVDC technology for synchronization of two interconnected thermal power grid of 12 areas when load disturbance occur in power grid-1. Three types of tie-lines HVAC–1HVDC parallel tie-line, HVAC– 2HVDC parallel tie-line and HVAC–3HVDC parallel tie-line are applied for synchronization of 12 area two interconnected thermal power grid. For synchronization purpose of power grid this research work shows the HVAC–3HVDC parallel tie-line is better as compare to the HVAC–2HVDC parallel tie-line and HVAC–1HVDC parallel tie-lie. This research work also shows the HVAC–2HVDC parallel tie-line is better as compare to the HVAC–1HVDC parallel tie-line. Quality of all three types of tie-line is judged by the frequency deviation of two interconnected power grid of 12 areas when load disturbance occur in power grid-1. The biggest advantage of this research work is that the two interconnected thermal power grid of 12 areas is Synchronize by HVDC technology with traditional integral controller.